Bronchopleural and pleurocutaneous fistula in HIV patient with pulmonary tuberculosis. (2017) - Duarte-Ribeiro, Filipa; Dias, Cátia; Mota, Margarida
Abstract: We present a 37-year-old man intravenous drug user, with HIV/HCV/HBV co-infection, lymph node tuberculosis 10 years before (completed 12 months of treatment), and left lobar pneumonia 4 years earlier complicated by empyema (treated with left lower lobectomy with a persistent bronchopleural fistula) who was admitted to the emergency department with caseous-purulent drainage and exteriorization of air from an orifice in the chest wall. Acid-fast bacilli were identified in this drainage. A pleurocutaneous fistula was evident on the chest computed tomography scan. He was admitted to the Infectious Diseases Unit and started on antituberculous therapy with a favorable outcome.